1995
DOI: 10.1111/j.1365-2141.1995.tb05593.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic study in multiple myeloma at diagnosis: comparison of two techniques

Abstract: Cytogenetic studies in multiple myeloma (MM) have been disappointing due to the low mitotic index of plasma cells. Recently the detection of clonal chromosomal abnormalities at diagnosis seemed to be improved by addition of cytokines (IL-6 and GM-CSF) in the culture medium. We performed two parallel total bone marrow cells culture types in 33 stage I, II and III multiple myeloma patients at diagnosis: 3 d without any cytokine, and 4-7 days stimulated with IL-6 and GM-CSF. No clonal chromosomal abnormality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
3
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 12 publications
4
48
3
1
Order By: Relevance
“…Eight large published series have been reviewed constituting 173 hyperdiploid karyotypes. 5,7,[14][15][16][17][18][19] The most frequently gained chromosomes were chromosomes 9 (156/173), 15 We then examined what would be the most sensitive and specific combination of three probes for the detection of hyperdiploidy. The analysis showed that the combination of chromosomes 5, 9, and 15 is the best compromise between specificity and sensitivity.…”
Section: Probe Selectionmentioning
confidence: 99%
“…Eight large published series have been reviewed constituting 173 hyperdiploid karyotypes. 5,7,[14][15][16][17][18][19] The most frequently gained chromosomes were chromosomes 9 (156/173), 15 We then examined what would be the most sensitive and specific combination of three probes for the detection of hyperdiploidy. The analysis showed that the combination of chromosomes 5, 9, and 15 is the best compromise between specificity and sensitivity.…”
Section: Probe Selectionmentioning
confidence: 99%
“…Deletions of the long arm of chromosome 13 (13q−), mostly at the q14 site, and monosomy of chromosome 13 are commonly described in MM PC as determined by conventional metaphase analysis, [1][2][3] comparative genomic hybridization 4,5 and multicolor metaphase FISH (SKY). 6,7 Tricot and colleagues have associated the presence of 13q− with an adverse prognosis in patients with MM 8,9 and proposed this genomic abnormality as one of the most important prognostic factors for MM patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to improve the detection of chromosomal abnormalities different cytokines have been used, however the incidence of abnormal karyotypes remains below 60%. [2][3][4][5] Comparative genomic hybridization (CGH) is a molecular cytogenetic technique that allows analysis of chromosomal copy number changes without the requirement of tumoral metaphases. 6 Accordingly, CGH would be particularly useful for identifying gains and losses of DNA sequences in tumors with a low proliferative index, such as MM.…”
Section: Introductionmentioning
confidence: 99%